2019
DOI: 10.1136/bmjopen-2018-028869
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a single-blind randomised controlled trial to evaluate the clinical effects of an Integrated Qigong exercise intervention on freezing of gait in Parkinson’s disease

Abstract: IntroductionQigong exercise offers a potentially safe, low-cost and effective mind–body rehabilitative intervention for mitigating the problem of gait interruption among patients with Parkinson’s disease (PD) who have frequent freezing of gait (FOG) episodes. However, its clinical effects have not been established. This paper describes the trial protocol of evaluating the clinical efficacy of a newly developed Integrated Qigong in improving gait among patients with PD who have FOG.Methods and analysisA single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…The format will be modeled after the experimental exercise format, including a 10-min warm-up, a 60-min exercise period with a 10-min break after the first 30 min, and 10-min cooldown (limb range-of-motion movements, sustained stretching, and relaxing). The balance training will consist of: (1) static balancing on unstable surfaces with the maintenance of postural control and progression to weight shifting; (2) dynamic balancing with postural control while standing and performing upper-limb and trunk movements; (3) balance strategy development with a focus on the hips while maintaining ankle balance, including stepping in different directions under interference; (4) and adaptation to varying bases of support and standing in a narrow space and on an uneven surface ( 31 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The format will be modeled after the experimental exercise format, including a 10-min warm-up, a 60-min exercise period with a 10-min break after the first 30 min, and 10-min cooldown (limb range-of-motion movements, sustained stretching, and relaxing). The balance training will consist of: (1) static balancing on unstable surfaces with the maintenance of postural control and progression to weight shifting; (2) dynamic balancing with postural control while standing and performing upper-limb and trunk movements; (3) balance strategy development with a focus on the hips while maintaining ankle balance, including stepping in different directions under interference; (4) and adaptation to varying bases of support and standing in a narrow space and on an uneven surface ( 31 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…The task will consist of randomly interleaved no-go and stop-signal trials, enabling us to examine both types of inhibition ( 32 ). A total of 480 trials (75% go, 17% stop, and 8% no-go) will be administered ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found that the practice of qigong exercises can have a positive effect motor function, walking ability and balance for individuals having Parkinson's disease [121][122][123][124][125][126].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“… 22 Li et al found that Health Qigong practice improved the ability to focus on the postural stability, and can enhance core muscle to stress weight-bearing joints and to increase proprioception input of trunk and lower limb joints. 23 Others showed that Health Qigong exercise relieved sleep disorders and non-motor symptoms in patients with PD. 24 The effect of Health Qigong on the mechanism of PD has attracted extensive attention from researchers worldwide.…”
Section: Introductionmentioning
confidence: 99%